STUDYING THE ROLE OF THE IL1β (Т31С) CYTOKINE GENE ALLELIC POLYMORPHISM IN THE MECHANISMS OF FORMATION OF GASTRIC AND DUODENAL ULCER - Tursunova Minavvar Ulugbekovna; Salaeva Muborak Saidobdullaevna; Halimova Holidа Hakimbaevna; Rustamov Makhmudjon; Musakov Mirzokhid Sabitdjanovich; Bobokulov Muhammad Fahriddinovich (Web of Journals Publishing, 2023)
Purpose: To assess the nature of the distribution of allelic and genotypic variants of the polymorphic gene IL1β (Т31С) Material and methods: The study was conducted with the participation of 100 patients with GU and DU, aged 20 to 84 years, who were hospitalized at the multidisciplinary clinic of the Tashkent Medical Academy in the period from 2019-2021, as well as 85 healthy individuals without gastrointestinal diseases. Results: We studied the features of the distribution of allelic and genotypic variants of the polymorphic cytokine gene IL1β (Т31С) in groups of patients with DU and GU compared with healthy ones. The study made it possible to determine the participation of unfavorable C allele and T/C and C/C genotypes in the pathogenetic mechanisms of DU development.
Keywords: IL1β (Т31С) cytokine gene polymorphism, alelle, genotype, gastric ulcer, duodenal ulcer.